Using Choice Experiments to Estimate the Value of Differentiated Cow's Milk in Puerto Rico - Tavárez, Héctor; Álamo, Carmen (Frontiers in Sustainable Food Systems, 2021)
In Puerto Rico, we use a choice experiment method through in-person interviews to estimate consumer willingness to pay (WTP) for a half gallon of cow's milk that is produced locally, friendly to the environment and with ethics in animal management. The results from a random parameters logit model show that consumers are willing to pay a premium of up to 41% for differentiated milk, indicating a potential market for these products. We also find that consumer's income and education, and number of dependents affect WTP estimates. Implications for the development of differentiated milk products are discussed.